2018
DOI: 10.1140/epjds/s13688-017-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the predictability of user demographics from cyber-physical-social behaviours in indoor retail spaces

Abstract: Understanding the association between customer demographics and behaviour is critical for operators of indoor retail spaces. This study explores such an association based on a combined understanding of customer Cyber (online), Physical, and (some aspects of ) Social (CPS) behaviour, at the conjunction of corresponding CPS spaces. We combine the results of a traditional questionnaire with large-scale WiFi access logs, which capture customer cyber and physical behaviour. We investigate the predictability of user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Society 5.0 as the Ultimate Cyber-Physical Society Both Industry 4.0 and Society 5.0 are premised on the creation of increasingly sophisticated "cyber-physical systems", which are characterized by their reliance on embedded, decentralized, real-time computation occurring within a network of heterogeneous physical objects (Gill 2008;Wang et al 2008). When human beings (or social robots or AIs) are functionally integrated into a cyber-physical system (CPS) at the social, cognitive, and physical levels, it becomes a "cyber-physical-social system" (CPSS) (Liu et al 2011) whose members may engage in "cyber-physical-social behaviours" within cyber-physical spaces (Ren et al 2018). Through their interactions with one another, the members of a CPSS may give rise to "cyber-physical social networks" whose topologies follow the members' social connections (Ganti et al 2008).…”
Section: Society 50 S Dependence On Transformative Future Technologiesmentioning
confidence: 99%
“…Society 5.0 as the Ultimate Cyber-Physical Society Both Industry 4.0 and Society 5.0 are premised on the creation of increasingly sophisticated "cyber-physical systems", which are characterized by their reliance on embedded, decentralized, real-time computation occurring within a network of heterogeneous physical objects (Gill 2008;Wang et al 2008). When human beings (or social robots or AIs) are functionally integrated into a cyber-physical system (CPS) at the social, cognitive, and physical levels, it becomes a "cyber-physical-social system" (CPSS) (Liu et al 2011) whose members may engage in "cyber-physical-social behaviours" within cyber-physical spaces (Ren et al 2018). Through their interactions with one another, the members of a CPSS may give rise to "cyber-physical social networks" whose topologies follow the members' social connections (Ganti et al 2008).…”
Section: Society 50 S Dependence On Transformative Future Technologiesmentioning
confidence: 99%
“…al. also found strong correlations between behaviours and user demography [188]. Further, it is also shown that the online and movement patterns can be used to predict the visiting intent of building occupants [189].…”
Section: Occupant Behaviour Modelingmentioning
confidence: 76%
“…Further, these features could also be used further for profiling users [27], useful for providing a personalised model to predict the visiting intent and next location indoors.…”
Section: Discussionmentioning
confidence: 99%